Perfil dos mestres de um programa de pós-graduação em Promoção de Saúde: características e percepções sobre o curso - Ferreira, Sara Regina (2014)
This study sought to identify the profile of master degree holders and their perceptions about their program, focusing on students who graduated from the Masters in Health Promotion at the University of Franca between January 2006 and May 2011. A semi-structured questionnaire, self-administered via emailed, was used as an instrument for data collection. Responses were obtained from 86 (67.1%) members of a sample of 128 graduates, composed predominantly of women (physiotherapists and nurses). The average age of the respondents when starting the program was 34 years and their average time to graduation was 25.6 ± 4,7 months. During their course of study, they worked over 40 hours per week as teachers in private higher education institutions, which served as sources of financial aid for the students. The respondents were characterized by poor performance in research, but they had a good command of English. Graduation contributed a salary increase of less than 20%, and teaching represented the predominant area of activity before and after the Masters. The expectations for the program were fully achieved. It was considered to be essential for professional practice, and the knowledge acquired is used in teaching. This study made it possible to know professionals with the skills and competencies necessary to solve current problems and to assist in the planning of better conditions for local communities.